2012
DOI: 10.15288/jsad.2012.73.120
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Americans Baseline Alcohol Survey (HABLAS): Effects of Container Size Adjustments on Estimates of Alcohol Consumption Across Hispanic National Groups

Abstract: ABSTRACT. Objective: This study was conducted to examine discrepancies in alcohol consumption estimates between a self-reported standard quantity-frequency measure and an adjusted version based on respondents' typically used container size. Method: Using a multistage cluster sample design, 5,224 Hispanic individuals 18 years of age and older were selected from the household population in fi ve metropolitan areas of the United States: Miami, New York, Philadelphia, Houston, and Los Angeles. The survey-weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Table 1 lists the characteristics and results from 20 typical consumption free-pour assessments. The typical consumption free-pour assessment has been conducted to assess the amount of alcohol individuals typically pour themselves in a variety of settings, including their homes (e.g., Caetano, Mills, & Harris, 2012; Lemmens, 1994), over the phone (e.g., Callinan, 2015), public locations (e.g., Boniface et al, 2013; Gill & Donaghy, 2004), health clinics (e.g., Kaskutas, 2000), and laboratories (e.g., Gill, Donaghy, Guise, & Warner, 2006). Although most typical consumption free-pour studies have focused on physical free-pours, typical consumption drink sizes have also been obtained by asking individuals to select photos of drinking glasses with lines most representative of their typical pour volumes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists the characteristics and results from 20 typical consumption free-pour assessments. The typical consumption free-pour assessment has been conducted to assess the amount of alcohol individuals typically pour themselves in a variety of settings, including their homes (e.g., Caetano, Mills, & Harris, 2012; Lemmens, 1994), over the phone (e.g., Callinan, 2015), public locations (e.g., Boniface et al, 2013; Gill & Donaghy, 2004), health clinics (e.g., Kaskutas, 2000), and laboratories (e.g., Gill, Donaghy, Guise, & Warner, 2006). Although most typical consumption free-pour studies have focused on physical free-pours, typical consumption drink sizes have also been obtained by asking individuals to select photos of drinking glasses with lines most representative of their typical pour volumes.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also assessed typical drink sizes across gender, with varying findings. For example, Caetano et al (2012) found women tended to pour larger portions of beer, wine, and liquor. In contrast, Carruthers and Binns (1992) found pours varied by type of drink, with men pouring larger portions of beer and liquor than did women.…”
Section: Typical Consumption Free-pour Assessmentmentioning
confidence: 99%
“…Yet a pronounced disparity remained at low levels of heavy drinking. Importantly, information on drink alcohol content is only just beginning to be integrated into research on racial/ethnic group drinking (e.g., see Caetano et al, 2012). Kerr et al (2009) previously found that models predicting alcohol problems had improved fit if they adjusted for measured drink ethanol, particularly models predicting alcohol consequences among blacks and dependence among Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Blacks have reported needing fewer drinks to feel intoxicated than whites, while Hispanics report more compared to whites [ 26 ]. Both blacks and Hispanics have reported higher-strength drinks than whites [ 27 , 28 ] and a larger number of drinks preceding perceived DUI [ 29 ].…”
mentioning
confidence: 99%